Human factor as operating safety dominant of ATM navigation support - Зайцев, Ю.В. (Proceedings of National Aviation University (archive), 2004)
The method of specifying individual psychophysical characteristics of the human higher nervous activity has been studied to match professional fitness. Information processing rate is being estimated considering peculiarities of the nervous system of the operators working in extreme situations, and providing fluent knowledge of Ukrainian, Russian and English.